The Effect of Capital Structure, Investment Decision and Working Capital Turn Over on Profitability - Siti Kustinah; Ines Aditia (Accounting and Finance Studies, 2023)
The purpose of this study is compare Capital Structure (DER), Investment Decision (MBVE) and Working Capital Turn Over (WCTO) on Profitability (ROA). The research method used is descriptive research with a quantitative approach. This population is property and real estate companies listed on the Indonesia Stock Exchange during the 2017-2021 period using the purposive sampling method and a 5-year observation period of 80 samples. The data source obtained is secondary data based on the results of IDX's annual financial reports. The analytical tool used is multiple linear regression analysis. The results of this study indicate that partially Capital Structure (DER) has a significant negative effect on Profitability (ROA), Investment Decision (MBVE) has a significant positive effect on Profitability (ROA), while Working Capital Turn Over (WCTO) has no effect on Profitability (ROA). . Simultaneously Capital Structure (DER), Investment Decision (MBVE) and Working Capital Turn Over (WCTO) have a significant effect on Profitability (ROA).